2007
DOI: 10.1179/174328507x163779
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics and mechanism of selective iron chlorination of an ilmenite ore

Abstract: The kinetics of the ilmenite chlorination was studied between 600 and 850uC. The ilmenite chlorination rate was determined by monitoring the mass changes using a thermogravimetric system of high resolution. Non-isothermal and isothermal runs were performed. The influence of temperature, chlorine flow and sample mass in the reaction rate was established. The thermal decomposition of ilmenite previous to the chlorination was taken into account. The formation of intermediate titanates during the chlorination reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It was determined that the yield of FeCl 3 was always one third of the Fe 2þ conversion. This was because O 2À ions cannot be replaced by Cl À below 600 C. 23,24) Two third of the Fe 3þ remained in combination with O 2À to meet the charge balance in the oxide lattice. The weight loss determined was in good agreement with the measured amount of Fe 3þ chlorinated.…”
Section: Oxidation Of Synthetic Ilmenitementioning
confidence: 99%
“…It was determined that the yield of FeCl 3 was always one third of the Fe 2þ conversion. This was because O 2À ions cannot be replaced by Cl À below 600 C. 23,24) Two third of the Fe 3þ remained in combination with O 2À to meet the charge balance in the oxide lattice. The weight loss determined was in good agreement with the measured amount of Fe 3þ chlorinated.…”
Section: Oxidation Of Synthetic Ilmenitementioning
confidence: 99%
“…Ilmenite modified by H 2 S was exploited by Zou et al as recyclable magnetic sorbent for the recovery of Hg up to five cycles, revealing highly efficient sorption of Hg in the temperature range 40–100 °C [10] . Generally, sulphate process and chloride process are well‐known for production of TiO 2 from ilmenite [11–12] . As the name indicates, in the first process the ilmenite is dissolved in sulphuric acid followed by Fe removal and hydrolyzed the titanium sulphate to hydrated TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the consumption efficiency of chlorine gas and the purity of TiCl4 can be improved by adding synthetic rutile with relatively high TiO2 content through the process of upgrading the ilmenite ore. Although a lot of studies on this selective chlorination method of ilmenite have been reported, there is a limit to clearly identify the rate-controlling step [1][2][3][4][5]. In this study, the reaction kinetics was analyzed by applying the unreacted nuclear model, and the variation in rate-controlling step on the selective chlorination of Fe in ilmenite ore through the addition of chlorine gas and coke was investigated.…”
Section: Introductionmentioning
confidence: 99%